Cigarette Smoking and Incident Stroke in Blacks of the Jackson Heart Study. Issue 12 (16th June 2020) - Oshunbade, Adebamike A.; Yimer, Wondwosen K.; Valle, Karen A.; Clark, Donald; Kamimura, Daisuke; White, Wendy B.; DeFilippis, Andrew P.; Blaha, Michael J.; Benjamin, Emelia J.; O'Brien, Emily C.; Mentz, Robert J.; Fox, Ervin R.; et al.
Abstract : Background: Blacks are disproportionately affected by stroke compared with whites; however, less is known about the relationship between stroke and cigarette smoking in blacks. Therefore, we evaluated the relationship between cigarette smoking and all incident stroke in the JHS (Jackson Heart Study). Methods and Results: JHS participants without a history of stroke (n=4410) were classified by self‐reported baseline smoking status into current, past (smoked at least 400 cigarettes/life), or never smokers at baseline (2000–2004). Current smokers were further classified by smoking intensity (number of cigarettes smoked per day [1–19 and ≥20]) and followed up for incident stroke (through 2015). Hazard ratios (HRs) for incident stroke for current and past smoking compared with never smoking were estimated with adjusted Cox proportional hazard regression models. After adjusting for cardiovascular risk factors, the risk for stroke in current smokers was significantly higher compared with never smokers (HR, 2.48; 95% CI, 1.60–3.83) but there was no significant difference between past smokers and never smokers (HR, 1.10; 95% CI, 0.74–1.64). There was a dose‐dependent increased risk of stroke with smoking intensity (HR, 2.28 [95% CI, 1.38–3.86] and HR, 2.78 [95% CI, 1.47–5.28] for current smokers smoking 1–19 and ≥20 cigarettes/day, respectively). Conclusions: In a large cohort of blacks, current cigarette smoking was associated with a dose‐dependent higher risk of all stroke. In addition, past smokers did not have a significantly increased risk of all stroke compared with never smokers, which suggests that smoking cessation may have potential benefits in reducing the incidence of stroke in blacks.